1989
DOI: 10.2172/7024835
|View full text |Cite
|
Sign up to set email alerts
|

Design and operation of an outdoor microalgae test facility

Abstract: Harvested productivity of M. minutum MONOR2.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
47
0
2

Year Published

1994
1994
2017
2017

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(50 citation statements)
references
References 3 publications
1
47
0
2
Order By: Relevance
“…It would thus appear that raceways should be as wide as practicable. The results thus support the recommendation from the US Energy Department study (34) of a length to width ratio of 11 to 1 for a raceway of ~1 hectare.…”
Section: Effect Of Depth and Velocity On Energy Ratiosupporting
confidence: 84%
See 1 more Smart Citation
“…It would thus appear that raceways should be as wide as practicable. The results thus support the recommendation from the US Energy Department study (34) of a length to width ratio of 11 to 1 for a raceway of ~1 hectare.…”
Section: Effect Of Depth and Velocity On Energy Ratiosupporting
confidence: 84%
“…Reducing the depth to 0.15 m may also not be practicable due to problems in grading the raceway bed (34). In this scenario, the head loss around the raceway was estimated at 0.082 m, slightly greater than the maximum differential head recommended by a paddlewheel manufacturer and half the recommended maximum mean depth as suggested by Oswald (45).…”
Section: Effect Of Factors Increasing Microalgal Concentrationmentioning
confidence: 90%
“…A recent model has shown that dynamic control of depth (0.1-0.5 m) and HRT (2-20 days) to match local and seasonal climatic conditions increased productivity by 0.6%-9.9% while decreasing water demand by 10%-61% compared to the standard approach of constant depth and HRT [50]. Raceways appear to produce stable cultures at 2 to 3 days HRT [51], but "crashes" regularly occur at 4 days [52]. Zamalloa, Vulsteke, Albrecht and Verstraete [20] recommended a HRT of 2 days and increasing this above 4 days may not be practicable for operational reasons.…”
Section: Maximum Harvesting Energy To Achieve a Net Energy Returnmentioning
confidence: 99%
“…This program, supported many basic research projects, including isolation of a large number of algal strains and investigation of biochemical and genetic aspects of lipid production in microalgae (SERI 1983(SERI ,1984(SERI , 1987a(SERI ,b, 1989NREL 1992). Three outdoor algal production facilities were supported by the ASP, in Hawaii (Laws et al, 1983(Laws et al, ,1986(Laws et al, ,1988, California (Benemann et al, 1981(Benemann et al, ,1983 and New Mexico, where two 0.1 hectare ponds (one lined and one unlined) were operated for two years Tillett, 1989, 1992).…”
Section: Ia3 the Doe -Seri Aquatic Species Programmentioning
confidence: 99%